Sustainable analysis of integrated cajuput oil business development as a sustainable forestry multi-business at PT Inhutani I - Ernawati, Titik; Syaufina, Lailan; Hariyadi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2021)
One of the consequences of deforestation is the spread of critical land both inside and outside the forest area. Agroforestry or intercropping is developed to provide benefits and improve welfare for the community, and to optimize the results of a form of sustainable land use to ensure and improve food needs. Eucalyptus is one type of plant that is suitable for forest land rehabilitation because of its ability to live on marginal lands. The purpose of the study was to assess the feasibility of eucalyptus oil business and formulate business sustainability development from seven aspects/feasibility parameters, which are namely: (1) legal aspects, (2) social, economic and cultural aspects, (3) market aspects, (4) management and human resources, (5) risk management aspects, (6) technical aspects, and (7) financial aspects. Meanwhile, to find out whether the eucalyptus business activity as a whole can be sustainable, and its development model, a sustainability analysis was carried out using the cobweb (Amoeba) method. Within the framework of sustainability, eucalyptus concessions must make changes and innovations (Estimated business feasibility on a planting area of 5,200 ha obtained a Net Present Value (NPV) of Rp. 950,734,956,062, - with a discounted interest rate of 12% shows that the eucalyptus oil industry will get a net profit of Rp 7,076,409,779,281, - BC Ratio of 12.56, Interest Rate of Return (IRR) of 55%, Payback Period in the 5th year 4 months shows that in a period of 5 years and 4 months from the investment can be returned from business revenues. The results showed that the seven aspects/parameters were declared feasible and continued with a sustainability analysis and concluded that the eucalyptus oil concession was declared sustainable.